COLLABORATIVE GOVERNANCE: OPTIMIZATION OF PUBLIC SERVICE PERFORMANCE THROUGH THE FUNCTION OF CUSTOMARY INSTITUTIONS - Alexander H. Badjuka; Sri Yulianty Mozin; Yacob N. Nani (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2024)
This research aims to explore the role of customary institutions in improving public service performance through a collaborative governance approach. By using collaborative governance theory and functionalism as analytical tools, this research analyses how the government, customary institutions, the community, and other stakeholders collaborate to achieve optimal public service goals. This research employs a descriptive qualitative method with primary and secondary data collection through literature review and interviews. The results show that customary institutions have a strategic role in strengthening the social legitimacy of policies, but still face structural challenges and a lack of formal recognition. This research provides recommendations to strengthen synergy between customary institutions and the government through collaborative governance strategies.